2011
DOI: 10.1186/1471-2458-11-21
|View full text |Cite
|
Sign up to set email alerts
|

Body image, body dissatisfaction and weight status in south asian children: a cross-sectional study

Abstract: BackgroundChildhood obesity is a continuing problem in the UK and South Asian children represent a group that are particularly vulnerable to its health consequences. The relationship between body dissatisfaction and obesity is well documented in older children and adults, but is less clear in young children, particularly South Asians. A better understanding of this relationship in young South Asian children will inform the design and delivery of obesity intervention programmes. The aim of this study is to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
73
6
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 50 publications
11
73
6
14
Order By: Relevance
“…Previous studies had suggested that childhood obesity was associated with a desire to be thinner whereas thinness was related to a desire to be heavier (10,13,34,35) . In other words, overweight and obese boys and girls tend to desire a thinner body image, while thin children usually desire to be heavier (or less thin).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had suggested that childhood obesity was associated with a desire to be thinner whereas thinness was related to a desire to be heavier (10,13,34,35) . In other words, overweight and obese boys and girls tend to desire a thinner body image, while thin children usually desire to be heavier (or less thin).…”
Section: Discussionmentioning
confidence: 99%
“…Body image perception, defined as 'the picture we have in our minds of the size, shape and form of our bodies; and our feelings concerning these characteristics and our constituent body parts' (8) , is one critical psychosocial factor that is related to body weight. While mostly investigated in the context of eating disorders, body image dissatisfaction (BID) is highly prevalent among healthy boys and girls (9)(10)(11)(12) . BID is associated with weight status, as heavier persons tend to be more dissatisfied with their body image compared with normal-weight people.…”
mentioning
confidence: 99%
“…A positive association between BMI and BSD has been observed in UK South Asian children as young as 5 years of age (14) . Children as young as 4 years have expressed negative attitudes towards a 'fat' body shape (15) and BSD is associated with restrained eating by the age of 9 years (17) .…”
mentioning
confidence: 94%
“…As for body image, the most consistently replicated finding is that obese children and adolescents have a more negative body image than their peers and often believe that they have been responsible for their obesity (Ben-Sefer et al, 2009). Overweight children as young as age 5 can also develop a negative body image (Pallan et al, 2011). A relationship between increasing weight status and body dissatisfaction in older children has been observed in many different cultural communities (Crow et al, 2006;Duncan et al, 2006;Fonseca et al, 2009;Mirza et al, 2005).…”
Section: Psychological Well-beingmentioning
confidence: 99%